The injury mechanism correlation between MRI and video-analysis in professional football players with an acute ACL knee injury reveals consistent bone bruise patterns - Pieter D’Hooghe (3530984) (2022)
Purpose To analyze the MRI features, in particular bone bruises pattern, of Anterior Cruciate Ligament (ACL) injured footballers, and to correlate them with the characteristics of injury mechanism and situation obtained from direct video footage. Methods Nineteen professional football (soccer) players that sustained ACL injury while playing during an official match of First League Championship were included in the study. The video of injury was obtained from the Television broadcast. Knee Magnetic Resonance (MRI) was obtained within 7 days from the injury. BB and meniscal lesions were analyzed on MRI, while a video-analysis of mechanisms of ACL injury and injury dynamic were assessed from the videos. Results The most commonly involved Bone Bruise areas in the knee were the Posterior Lateral Tibial Plateau (LTp) in 16 cases (84%) and the Central Lateral Femoral Condyle (LFc) in 11 cases (58%). Three patients (16%) had bone bruise in the Posterior Medial Tibial Plateau (MTp) while none (0%) had bone bruise in the Medial Femoral Condyle. Based on the bone bruise pattern, 11 (58%) had simultaneous LFc and LTp and were defined “Typical” while 8 (42%) had other locations or no bone bruise and were defined “Atypical”. 9 out of 11 injuries (82%) of athletes with “Typical” pattern occurred with a “Pivoting” action”, in contrast to only 1 case (12%) in those with “Atypical” bone bruise pattern (p = 0.0055). The most common situational mechanism pattern on video analysis was “pressing” (n = 7) accounting for the 47% of the “indirect” ACL injuries. In terms of movement pattern, ten injuries (52%) occurred during a “Pivoting” movement (7 pressing, 1 dribbling, 1 tackled, 1 goalkeeping), whereas the remaining were classified as “Planting” in four cases, “Direct Blow” in four cases and “Landing”. Conclusion A well-defined and consistent bone bruise pattern involving the posterior tibial plateau and central femoral condyle of lateral compartment is present in footballers that sustained non-contact and indirect ACL injuries during pivoting with sudden change of direction/deceleration, while heterogeneous patterns were present in those with direct contact or injury mechanisms involving high horizontal velocity. Level of evidence Level IV. Other Information Published in: Knee Surgery, Sports Traumatology, Arthroscopy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00167-022-07002-6